Caracterização dos processos hidromorfológicos em uma região de variação abrupta de relevo - Pereira, Gabriel Sulzbach (2024)
The step-pool configuration represents the characteristic bed morphology dominating channels in mountainous regions, exerting control over the flow and sediment dynamics of downstream rivers. Changes in land use and the effects of climate change can destabilize this configuration, leading to impacts such as landslides, floods, and alterations in sediment transport, affecting the ecosystem of these channels and the communities downstream. Despite the significance of this topic, there is a scarcity of studies related to this area in Brazil, with analyses often relying on data extrapolated from other regions. Due to the complexity of mountainous environments, the stability of step-pool channels is commonly assessed through morphological approaches combined with hydraulics. Using empirical equations, it is possible to estimate the critical hydrological condition for system destabilization, in the form of critical velocity for the threshold movement of boulders on the steps, a parameter whose estimation also varies due to different methodologies of measurement. This study aimed to investigate uncertainties related to stability estimation in a typical step-pool channel of the Plateau Edge. Results compared 11 empirical critical velocity equations using three distinct methodologies to determine the characteristic step grain size: direct measurement, Pebble Count, and image analysis. Findings revealed considerable variations among empirical equations and methodologies, reaching a 100% variation between different grain characterization approaches. The significant uncertainties identified indicated limitations in the methodology used for stability analysis, emphasizing the need for more detailed and specific studies. A more in-depth approach can guide effective management and planning of water resources in mountainous areas, enhancing community safety against landslides and other impacts.